2018
DOI: 10.3758/s13414-018-1577-9
|View full text |Cite
|
Sign up to set email alerts
|

The hard work of doing nothing: Accounting for inhibitory costs during multiple action control

Abstract: Performing many actions at the same time is usually associated with performance costs. However, recent eye-tracking evidence indicates that under specific conditions, inhibiting a secondary response can be more costly than executing it, resulting in dual-action benefits. Here, we show that performance gains due to the absence of inhibitory control demands in dual-action trials are not limited to saccades as a response modality. In our study, participants had to react to a visually presented directional word by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…In line with previous studies, we observed dual-action benefits in the ERs for the manual modality, but dual-action costs in the RTs for the vocal modality 7 (for an in-depth discussion of possible underlying mechanisms, see Raettig & Huestegge, 2018). However, this partial replication was accompanied by a notable change: We now also observed dual-action benefits in the RTs for the manual modality.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with previous studies, we observed dual-action benefits in the ERs for the manual modality, but dual-action costs in the RTs for the vocal modality 7 (for an in-depth discussion of possible underlying mechanisms, see Raettig & Huestegge, 2018). However, this partial replication was accompanied by a notable change: We now also observed dual-action benefits in the RTs for the manual modality.…”
Section: Discussionsupporting
confidence: 91%
“…To this end, we made use of the same basic paradigm implemented by Raettig and Huestegge (2018) with some minor modifications and extended it with an expectancy manipulation by systematically varying the frequency of certain action demands (see below). Participants encountered directional words ("links"/ "left" and "rechts"/"right") as stimuli and reacted by either (a) reading the word aloud (single-vocal response condition), (b) pressing the left or right arrow key on the keyboard according to the meaning of the word (single-manual response condition), or (c) executing both actions at the same time (dual response condition).…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This paradigm did not involve a no-go stimulus, but just consisted of intermixed single-and dual-response trials triggered by the same aspect of a single stimulus (thus, this study was different from a typical dual-task setup). These results also highlight the role of automaticity: The more automatic a response is, the harder it is to suppress, eventually leading to greater cognitive costs of inhibition (doing nothing) than of overt execution (see also Raettig & Huestegge, 2016). As in the present study, automaticity was assumed to increase the tendency to translate a stimulus into a response (similar to advance preparedness, based on the fact that a no-go stimulus is presented second or that Task 2 is a simple go/no-go task with only one response alternative).…”
Section: Relation To Other Studiesmentioning
confidence: 76%
“…The present results can also be related to other phenomena. For example, a reduction in dual-task costs in Task 1 was also reported when saccadic eye movements were required in Task 2 as compared with keeping the eye fixated at the screen center (Huestegge & Koch, 2014; see also Raettig & Huestegge, 2018). These studies assumed that a saccadic eye movement toward a peripheral target occurs rather automatically, and thus inhibition is needed to keep the eye fixated at the screen center.…”
Section: Relations To Other Phenomenamentioning
confidence: 91%